Fenomena sindrom nomophobia dan dampaknya terhadap kualitas kecerdasan majemuk pada anak usia dini - Novi Mulyani (Pusat Studi Gender dan Anak (PSGA) IAIN Purwokerto, 2023)
This study reveals the impact of nomophobia syndrome on the quality of early childhood multiple intelligences in students at R.A. Perwanida Tamansari Karanglewas Banyumas. The research method used is descriptive qualitative by relying on data sourced from research informants through interview, observation, and documentation techniques. The main informants in this study were six students and their parents who were determined by purposive sampling. The findings of this study are (1) Nomophobia syndrome in students at RA Perwanida Tamansari Karanglewas was not found in its entirety. However, based on existing qualitative indicators, it can be classified into two types, namely students who have the potential to have nomophobia syndrome and students who have symptoms that lead to nomophobia syndrome; (2) The dominant multiple intelligences in students at R.A. Perwanida Tamansari Karanglewas there are six intelligences, namely spiritual intelligence, language intelligence, kinesthetic intelligence, musical intelligence, interpersonal intelligence and logical-mathematical intelligence. The six intelligences are seen when students carry out school activities either through routine activities, spontaneous activities, or exemplary activities; and (3) The impact of nomophobia syndrome on students at RA Perwanida Tamansari Karanglewas on three children's multiple intelligences, namely, first, students who are potentially affected by the nomophobia syndrome do not see a significant impact on their language, kinesthetic and interpersonal intelligence. Second, students who lead to mild symptoms of nomophobia syndrome seem to have an impact on language intelligence and interpersonal intelligence. As for kinesthetic intelligence, it looks pretty good.